Pengaruh Paparan Iklan Ultra-Processed Food terhadap Preferensi dan Perilaku Makan Anak Usia Sekolah: Kajian Literatur Sistematis - Nyoman Wahyu Meta Wulandari; Kadek Dyah Swasni Prambandita (Lembaga Pengembangan Kinerja Dosen, 2025)
Exposure to food advertising, particularly UPF (Ultra-Processed Food), not only impacts children's short-term food choices but also influences the formation of long-term unhealthy eating habits. Several studies have found that advertising's influence on children is not only direct but is also reinforced by environmental factors such as family eating habits, peer influence, and food accessibility at home and school. For example, children who regularly watch television unsupervised or who have personal devices with internet access are more likely to be exposed to UPF advertising, which is typically designed with bold colors, cartoon characters, and memorable slogans. This makes children more susceptible to influence and develop preferences for the promoted foods. Furthermore, UPF advertising often features emotional messages or positive associations such as fun, friendship, and rewards, further strengthening its appeal to children. When these advertisements are repeatedly exposed, children can internalize these messages and make them part of their eating experience. In the long term, this risks causing children to associate unhealthy foods with comfort or happiness, which can trigger emotional eating and increase the potential for eating disorders and the risk of non-communicable diseases. Therefore, it is crucial to involve various stakeholders, including parents, educators, industry players, and policymakers, in building a healthy eating environment. Media literacy education for children is also a crucial step in equipping them to be more critical of advertising messages. Strict regulations on food marketing aimed at children, such as banning UPF advertising during children's broadcast hours, regulating the use of cartoon characters, and providing clear and easy-to-understand nutrition labeling, are important strategies to reduce the negative impact of UPF advertising on children's health in the long term.